2002
DOI: 10.1098/rspb.2002.2000
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection constrained by life history in a butterfly

Abstract: Trait evolution via sexual selection has traditionally been viewed as isolated from life-history constraints. Recent theoretical treatments, however, predict that costly sexually selected characters should be mediated by the same allocational trade-offs that apply to more conventional aspects of reproductive investment. Participation in risky competitive behaviours, for example male-male combat, should therefore increase as the opportunity for future reproduction declines. However, the demonstration of such tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 30 publications
1
55
1
Order By: Relevance
“…Nevertheless, trait evolution via sexual selection has traditionally been viewed as isolated from life-history constraints (Hö glund & Sheldon 1998;Kokko 1998;Candolin 2000;Kemp 2002a;Kokko et al 2002). Recent theory, however, predicts that sexually selected characters should be subject to the same allocation trade-offs that apply to more traditional life-history traits (Enquist & Leimar 1990;Kemp 2002aKemp , 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, trait evolution via sexual selection has traditionally been viewed as isolated from life-history constraints (Hö glund & Sheldon 1998;Kokko 1998;Candolin 2000;Kemp 2002a;Kokko et al 2002). Recent theory, however, predicts that sexually selected characters should be subject to the same allocation trade-offs that apply to more traditional life-history traits (Enquist & Leimar 1990;Kemp 2002aKemp , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theory, however, predicts that sexually selected characters should be subject to the same allocation trade-offs that apply to more traditional life-history traits (Enquist & Leimar 1990;Kemp 2002aKemp , 2006. Consequently, there has been a concerted effort towards viewing the processes and outcomes of sexual selection from a life-history perspective in recent years (Hö glund & Sheldon 1998;Kokko 1998;Kemp 2002aKemp , 2006Kokko et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In females, the abdomen was seen distinctly larger than that of the males as described by Collins and Morris (3) . The inner margin of the hind wings had tufts of hair in the males, which are actually the scent scales from where the pheromones were released during the time of mate selection (16) . Haribal (4) reported that the total life cycle of P. aristolochiae was completed within ± 30 days in laboratory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This species was observed to lay the eggs singly as was the case with most papilionid butterfly species (15) . The single egg-laying habit has an advantage in that it averts the possibilities of larval saturation by resource exhaustion and enables effective utilization of isolated plants (16) . In the absence of suitable tender leaves, the female preferred to oviposit on tender shoots.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are also several species, including P. aegeria, where body size does not affect contest outcome (Lederhouse 1982;Kemp 2000;Takeuchi 2006a,b;Bergman et al 2007). Age can also influence the outcome of territorial contest, with older males having higher contest persistence in some species (Kemp 2002), while younger males have an advantage in other species (Kemp 2003). Yet, in some other species, including P. aegeria, age has no or little effect on contest resolution (Kemp et al 2006a;Takeuchi 2006b;Bergman et al 2007).…”
Section: Introductionmentioning
confidence: 99%